Information Technology and Electronic Commerce Investments, Time Trends of the Speeds of Adjusting the Actual Toward the Maximum Pay, and Chief Executive Officer Compensation - Lin, Winston T.; Chen, Yueh H. (Journal of Applied Business and Economics, 2024)
This research analyzes the effects of information technology (IT) and e-commerce (EC) investments and trends of the speeds of adjusting the observed toward the desired CEO pay in US firms, based on the adjustment model and its associated adjustment valuation (AV) approach, where the adjustment speeds are assumed dynamic and variable. The findings include: the speeds of adjusting the observed toward the unobserved compensation are fast; either IT or EC appearing alone or jointly impacts CEO compensation; the trends of adjustment speeds are nonlinear and nonstationary; and overall, the US CEOs tend to underpay during the period under study; among others.